Humour as a new social movement of start-up workers on @Ecommurz Instagram - Anang; Dicky Wahyudi; Purwandi, Edeliya Relanika (Faculty of Communications Science, Dr. Soetomo University, 2025)
This study examined the discourse of a new social movement of start-up workers through the modality of humour produced by the Instagram account @Ecommurz Indonesia. Using multimodal critical discourse analysis of a 150-content corpus in 2023, this analysis focuses on ideational, interpersonal, and textual symbols. This finding shows that humour on @ecommurz serves as a mobilisation engine for startup workers. Six prominent ideas were identified: labour exploitation, low income, divestment, investment, petitions, and layoffs. Visually, direct eye contact, parallel angles, and popular personas reduce audience distance, while the opening-interruption-closing narrative pattern, clean typography, contrast in meaning, and hashtags unify interpretation and accelerate dissemination. Intertextuality (brand parody, political nostalgia) strengthens critical power and sarcasm. This combination produces shareable humour with criticism, builds collective identity and shared memory, and triggers organic participation on social media. Thus, humour expands cross-professional coalitions and affirms its role as a repertoire of new social movements on social media, particularly in the discourse of Indonesian start-ups.